An experimental and theoretical investigation of Co-containing hydroxyapatites prepared at different temperatures - Gur, Vahit; Tatar, Cengiz; Kaygili, Omer; Bulut, Niyazi (Springer, 2022)
In the present paper, the effects of various calcination temperatures of 675, 775, 875, and 975 degrees C on the structural properties of 0.8 at.% Co-containing hydroxyapatites (HAps) were investigated by using X-ray diffraction (XRD) analysis, Fourier transform infrared (FTIR) spectroscopy, differential thermal analysis (DTA), and scanning electron microscopy (SEM). A density functional theory (DFT) has been applied to find out the energy band gap and density of states (DOS). It was found that the crystallite size and lattice strain gradually increased with increasing temperature. For each sample, biphasic structure was observed. The phase distribution was affected by the temperature. The significant changes, dependent on the calcination temperature, in the crystallinity percent, stress, and anisotropic energy density values were detected. The functional groups of phosphate and hydroxyl associated with the formation of the HAp phase were detected for each sample. It was observed that the calcination temperature affected the morphology.
Keywords: Hydroxyapatite; Sol-gel synthesis; X-ray diffraction (XRD); Scanning electron microscopy